Remarques de Jean-Claude Risset - Risset, Jean-Claude (Musica/Tecnologia, 2010)
Jean-Claude Risset analyzes the role of computer science in relation to the creation of music, highlighting the need for the composers to create their ‘own’ resources through a specific research activity, similar to what happened in the path that has seen the birth and development of the electric technologies and, later, of the digital ones. Activities that can and should – thanks to the possibilities increasingly offered today by programming languages – be kept alive, so that we can achieve a new type of complementarity between the composer and the work, as called for by Célestin Deliège.